Studies on the incidence of Reproductive Abnormalities in Local non-descript Female Goats - SHEKHAR REDDY, K CHANDRA; REDDY, V SUDHIR CHANDRA; RAO, A SESHAGIRI; REDDY, J MURALIDHAR; SHARMA, G P (The Indian Journal of Animal Reproduction, 2023)
An abattoir study was done on the local non-descript female goat genitalia to study the incidence of various forms fgynaecopathological condition~ and the same was worked out to be 10.86 percent. The detailed incidence of various types of gynaeco-pathological conditions are as follows: Hypoplasia of ovary (0.03 per cent); Abnormalshape of ovary (0.03per cent); double external os of cervix (0.10 per cent); Bent cervix ( 1.70per cent); uterus unicornis (0.03 per cent); Parovarian cysts (2.22 per cent); ovarian cyst&(0.27 per cent); ovaro-bursal adhesions (0.31per cent); salpingitis (0.51 per cent);Hydrosalpinx (0.20 per cent); Endometritis (3.?-1percent); Hydrometra (0.06 per cent); Melanin pigmentation (0.06 percent); False extra-uterinepregnancy (0.03 per cent); Foetal mummification (0.06 per cent); foetal maceration (0.03 percent); Foetal anasarca . (0.03 per cent); Anky losed muscle contracture monster (0.3 percent) and Hydrocephalus (0.03 per cent).
Keywords: Reproductive Abnormalities; Female Goats